2017
DOI: 10.1002/dvg.23009
|View full text |Cite
|
Sign up to set email alerts
|

Developmental transcriptional regulation by SUMOylation, an evolving field

Abstract: SUMOylation is a reversible post-translational protein modification that affects the intracellular localization, stability, activity, and interactions of its protein targets. The SUMOylation pathway influences several nuclear and cytoplasmic processes. The expression of many genes, in particular those involved in development is finely tuned in space and time by several groups of proteins. There is growing evidence that transcriptional regulation mechanisms involve direct SUMOylation of transcriptional-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…Indeed, the covalent attachment of SUMO modifiers essentially affects the intramolecular and intermolecular interactions of substrate proteins, thereby altering their activity, subcellular localization, or stability. Functionally, SUMOylation plays a paramount role in the regulation of gene transcription, since most of its targets are transcription factors, transcriptional co-regulators, chromatin-remodeling proteins, and DNA repair enzymes 104 . As the expression of SUMO-conjugating enzymes is frequently deregulated in cancer 105 , and several EMT-inducing transcription factors are well-known targets of the SUMOylation machinery 106 , it is tempting to speculate that SUMOylation may be a driving force behind the plasticity of invasive carcinoma cells.…”
Section: Novel Signaling Mechanisms and Trascription Factors Promotinmentioning
confidence: 99%
“…Indeed, the covalent attachment of SUMO modifiers essentially affects the intramolecular and intermolecular interactions of substrate proteins, thereby altering their activity, subcellular localization, or stability. Functionally, SUMOylation plays a paramount role in the regulation of gene transcription, since most of its targets are transcription factors, transcriptional co-regulators, chromatin-remodeling proteins, and DNA repair enzymes 104 . As the expression of SUMO-conjugating enzymes is frequently deregulated in cancer 105 , and several EMT-inducing transcription factors are well-known targets of the SUMOylation machinery 106 , it is tempting to speculate that SUMOylation may be a driving force behind the plasticity of invasive carcinoma cells.…”
Section: Novel Signaling Mechanisms and Trascription Factors Promotinmentioning
confidence: 99%
“…If TnaA is influencing BRAHMA BAP complex function, it may act close to the promoter or on regulatory elements such as enhancers where BAP complexes are remodeling chromatin. TnaA may also have other targets than the BAP complex and have a wider target specificity as has been shown for other E3 SUMO ligases (reviewed in [ 8 ]). These are questions still unanswered and for example, chromatin immunoprecipitation experiments with TnaA antibodies that recognize specific isoforms at different times of development, will be helpful to start to determine the range of action of these TrxG proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there are several types of E3 ligases that choose or help the SUMOylation of a target protein. SUMOylation of a target protein can change its sub-compartmentalization within the cell or nucleus, can favor a change of partners and/or it can label it for degradation (revised in [ 8 ]). The PIAS (Protein Inhibitors of Acivated STAT [Signal Transducers and Activators of Transcription]) family is a subgroup of E3 SUMO ligases that interact physically with E2 enzymes through a canonical 42 amino-acidic residues SP-RING (Siz/PIAS-Really Interesting) zinc finger [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functions of proteins can be achieved by post-translational modification, for example with small ubiquitin-related modifier (SUMO) [ 35 , 36 ]. We previously demonstrated that the function of Prox1 as a co-repressor might be inhibited by sumoylation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%